2015
DOI: 10.4236/mps.2015.51001
|View full text |Cite
|
Sign up to set email alerts
|

Lower Blepharoplasty Review, Transcon-junctival vs. Transcutaneous Approach

Abstract: Currently in lower blepharoplasty, the transconjunctival approach indication has been limited to young patients without skin excess and prominence of bags; in our practice this access has become the preferred technique in most of our cases because it is simpler, faster, prevents bad scarring, produces less orbicularis muscle trauma, and decreases postoperative edema and possible retractions (ectropion) in patients with decreased lower palpebral tone. Objective: To identify important concepts when deciding this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…These researchers suggested the transconjunctival lower lid blepharoplasty as it circumvents the risk of lower eyelid retraction associated with the transcutaneous approach (Jacono et al 2001). A lower rate of complications reported via the transconjunctival approach, with greater patient satisfaction (Rancati et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These researchers suggested the transconjunctival lower lid blepharoplasty as it circumvents the risk of lower eyelid retraction associated with the transcutaneous approach (Jacono et al 2001). A lower rate of complications reported via the transconjunctival approach, with greater patient satisfaction (Rancati et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The transconjunctival and approaches were preferred in 42 and 58 % (Rancati et al 2015). In transconjunctival versus transcutaneous lower eyelid blepharoplasty (Netscher et al 1995) in 6 months follow-up reported 10 consecutive patients presented for blepharoplasty, and in all patients the transcutaneous subciliary musculocutaneous fl ap approach was used on the left lower eyelid and the transconjunctival preseptal approach was used on the right.…”
Section: Discussionmentioning
confidence: 99%
“…Other complications include infection, scleral show, conjunctivitis, corneal ulcer, diplopia, amaurosis, and damage of both the inferior oblique muscle and the orbicularis oculi muscle. According to the results of Rancati et al, 12 insufficient lipectomy is more common in the transconjunctival group than in the transcutaneous blepharoplasty group. On the other hand, overresection of the fat pads frequently results in the hollowing of the infraorbital region along with the worsening of the lower eyelid wrinkles.…”
Section: Carbon Dioxide Laser-assisted Transconjunctival Lower Blephamentioning
confidence: 98%
“…The main risk point is difficulty in bleeding control. 12 Meticulous hemostasis is critical during the entire procedure. The blood vessels associated with each fat compartment must be cauterized.…”
Section: Carbon Dioxide Laser-assisted Transconjunctival Lower Blephamentioning
confidence: 99%
See 1 more Smart Citation